(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article gives information about synonymy as semantic relation in many different languages. It is considered necessary for a speaker with a certain competence to know not only the meaning of a word but also its interaction with other words in the language, that is, antonymic, hyponymy, and synonymic relations. The expression and fixation of these relations are often regarded as one of the main tasks of lexical semantics. Paradigmatic relations of synonymy, antonym, and hyponymy represent the harmonization of lexical elements. Hyponymy is one-sided, which means that the signs of a superior word are expressed in the meaning of a subordinate word.